Seminal mini-cutting in Sarcomphalus joazeiro (Mart.) Hauenshild (Research, Society and Development, 2021)
Sarcomphalus joazeiro (Mart.) Hauenshild is a plant native to the Caatinga biome that stands out for its ecological importance, use as an ornamental plant, manufacture of commercial products, animal and human consumption due to its nutritional and medicinal properties. The propagation of S. joazeiro by seeds, has as limitations the difficulty of obtaining dispersion propagules in periods of long drought, rapid decline in germination power, the need to overcome seed dormancy caused by the hard and resistant endocarp, the main method being used is concentrated sulfuric acid, increasing the cost and risks of its manipulation and contamination of the environment. An alternative for the propagation of this plant is the use of the mini-cutting technique from juvenile material of seminal origin, due to the independence of seeds for the production of seedlings. In view of the above, this research aimed to form and evaluate a mini-clonal hedge of seminal origin of the species S. joazeiro in its first year of establishment. Initially, an experimental S. joazeiro mini-clonal hedge was established, and then the technical evaluation was established. The mini-stumps survival rate of the S. joazeiro mini-clonal hedge was 100% and the average productivity in its first year of evaluation was good (7.9 mini-cuttings / mini-stumps), indicating that this clonal propagation technique has the potential to be adopted.